Icarus and Jonah: Flight and Containment in Cendrars's Work - Nicole Dupré (Studies in 20th & 21st Century Literature, 1979)
The study of two dreams and other related texts will show the ambivalent dynamism of Cendrars's imaginary universe. The first dream is a claustrophobic nightmare. The evident symbolism of the images reveals Cendrars's visceral need for changes and evasion as well as his constant rejection of limits. Both life and work follow the dynamics of escape and promote an ideology of separation. The second dream is a dream of flight. Its symbolism and the numerous thematic variations encountered stress the dynamics of ascension and outline an ideology of the quest, complementary to the first dream. This attitude is defined as an Icarus complex, the metaphysical dimension of which explains Cendrars's disappointment with action and adventure. A third group of figures suggests a new direction for Cendrars's aspirations, now related to the dynamics of fall. A strong desire for isolation and reclusion bears witness to a Jonah complex. Torn by contradictory longings, Cendrars's split personality cannot experience unity except in a very transitory and frail stage such as the ambulatory cell or the dark room of imagination. Only writing, Cendrars's voluntary prison as well as spiritual adventure, allows the author to transcend the original dilemma.
Keywords: Blaise Cendrars; isolation; escape